RESPON TERHADAP REGULASI PERKAWINAN DI INDONESIA - Sakirman (AS-SALAM, 2013)
Based on historical records, the demand to change the rules of marriagein Indonesia from pre-independence till now was initiated by the women’smovement and feminist. These cases had have at the beginning of the 20thcentury that women’s movement has influenced the world women in the3rd world. Thus, it have an effect for open the eyes of many people over theoppression of women as a result of the rules of conventional marriage andthe need for enforcement of women’s rights.